The Departure of the Guardian (Wali) after Taukil al-Wali in a Marriage Contract Ceremony in Batursari, Talun, Pekalongan: A Legal Anthropology Study - Mundzir, M. Afief; Sagaf, Muhammad; Rofiq, Ahmad; Yahya, Imam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Taukil al-wali is delegating marriage guardianship rights to the office of Religious Affairs (KUA) officials or community leaders. The local community widely accepts this practice because religious and traditional leaders legitimize it. This study aims to examine the community's view of the departure of the guardian (wali) after taukil al-wali and review this phenomenon from the perspective of legal anthropology. The research used a qualitative method with a legal anthropology approach. Data were obtained through observation, interviews, and documentation. The findings show that the people of Batursari Village view marriage as a sacred event, so the guardian delegating his marriage guardianship rights to KUA officials or community leaders is considered to have to leave the assembly for the marriage contract ceremony. This view is based on a limited understanding of the law of taukil al-wali, the influence of religious leaders, and respect (tabarukan) for those given a mandate. The guardian's departure is considered a valid condition for marriage; if not fulfilled, the marriage is deemed invalid and must be repeated. Local cultural values also influence this practice. Unwritten customary law becomes the community's main guideline in taukil al-wali. The strong influence of cultural values causes people's compliance with customs more dominant than formal rules. In conclusion, the guardian's departure after taukil al-wali reflects religious norms and local cultural integration. The legal anthropology perspective shows the important role of custom in shaping the distinctive marriage practices in the Batursari Village community.